Construction of Knowledge Test to Measure the Knowledge Level of Farmers about Digital Technologies - Ohlan, Manisha; Dahiya, Manju (Journal of Agricultural Extension Management, 2022)
Knowledge is a familiarity, awareness or understanding of someone or something such as facts, information, descriptions or skills which were acquired through experience or education by perceiving, discovering or learning. To measure the knowledge level of farmers regarding digital technology in their agriculture farm, a knowledge test was developed on the basis of thinking and differentiation of well-informed farmers than poorly informed ones. Total of 37 items covering a list of digital technology was constructed. The obtained scores from each items were used for item analysis comprising item difficulty index and discrimination index. Total 21 items were selected in final scale having difficulty index ranging 20-80 and discrimination index above 0.20. Reliability of knowledge test was measured by split half method. The coefficient of correlation value in split half was 0.80 at 1 per cent level of significance. Developed knowledge test was found to be highly stable and dependable measurement